Falls and associated factors among elderly users of Primary Healthcare Services - Scarlet Feitosa Santos; Miriane Lucindo Zucoloto; Natalia Akemi Yamada Terada; Edson Zangiacomi Martinez (Revista Brasileira de Atividade Física e Saúde)
The objective of this cross-sectional study was to estimate the self-reported prevalence of falls among elderly users (older than 60 years) of the Ribeirão Preto, São Paulo, Brazil, primary healthcare services in the past six months and to identify associated factors. Data were collected from five healthcare districts by means of personal interviews with the users while they waited for the appointment. Log-binomial regression models adjusted for confounding variables and prevalence ratios were used to measure the association between independent and dependent variables. The International Physical Activity Questionnaire (IPAQ), adapted to elderly, was used to assess their physical activity. A total of 357 adults were interviewed, with 62.7% being women and mean age of 69.9 years old. The prevalence rates of falls in the past six months were 19.6% (95%CI: 13.2–27.3) and 32.6% (95%CI: 26.4–39.2), respectively, for men and women. e prevalence of falls among users with lower level of physical activity was 2.3 times higher than that among those with higher level of physical activity (RP = 2.3; 95%CI: 1.4–3.8) after adjustment for gender, age group and socio-economical class. In conclusion, falls are frequent among the elderly and the practice of physical activities can improve their health condition, thus preventing the occurrence of falls.